Evaluation of Arterial Stiffness Using Pulse Wave Velocity and Augmentation Index in Patients with Chronic Venous Insufficiency. (2nd December 2018) - Dogdus, Mustafa; Akhan, Onur; Ozyasar, Mehmet; Yilmaz, Ahmet; Altintas, Mehmet Sait
Abstract : Background and Objectives . Chronic venous insufficiency (CVI) is a common pathology of the circulatory system and is associated with a high morbidity for the patients and causes high costs for the healthcare systems. Arterial stiffness has been shown to be a predictor of cardiovascular events and mortality. The relationship between CVI and arterial stiffness using pulse wave velocity (PWV) and augmentation index (Aix) was evaluated in this study. Methods . Sixty-two patients with the stage of C3-C5 chronic venous disease (CVD) and 48 healthy subjects were enrolled in the study. To assess arterial stiffness, all cases were evaluated with I.E.M. Mobil-O-Graph brand ambulatory blood pressure monitor device. PWV and Aix were used to assess arterial stiffness in this study. Results . The mean age was 61.9±11.05 years and 54 % of the patient population was females. PWV and Aix were significantly higher in CVI patients than controls (8.92±1.65 vs. 8.03±1.43, p=0.001; 25.51±8.14 vs. 20.15±9.49, p=0.003, respectively) and also positive linear correlation was observed between CVI and all measured arterial stiffness parameters (r=0.675 for CVI and PWV, r=0.659 for CVI and Aix, respectively). A PWV value of > 9.2 has 88.9 % sensitivity and 71.4 % specificity to predict the presence of CVI. Conclusions . PWV and Aix are the most commonly used, easy, reproducible, reliable methods in the clinic to assess arterial stiffness. Logistic regression analysis showed that PWV and Aix were the independent predictors of CVI. PWV has the sensitivity of 88.9 % and specificity of 71.4 % to detect the presence of CVI.